2020
DOI: 10.3389/fgene.2020.00936
|View full text |Cite
|
Sign up to set email alerts
|

NRG1, PIP4K2A, and HTR2C as Potential Candidate Biomarker Genes for Several Clinical Subphenotypes of Depression and Bipolar Disorder

Abstract: Genetic Associations for Subphenotypes of Mood Disorders Bioinformatic functional annotation of associated variants revealed possible impact for transcriptional regulation of PIP4K2A. In addition, the allele A of rs2248440 (HTR2C) may be a prognostic biomarker of depression severity. This allele decreases expression of the neighboring immune system gene IL13RA2 in the putamen according to the GTEx portal. The variant rs2248440 is near rs6318 (previously associated with depression and effects of psychotropic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 132 publications
0
11
0
Order By: Relevance
“…PI4K2A also regulates VAMP3 involved in vesicular trafficking and GH secretion, which is already reported in rat pituicytes [38]. Protein PIP4K2A is involved in neuronal signal transduction and is a critical regulator for intracellular cholesterol transport [39], which has been reported as a biomarker gene candidate in bipolar disorder and depression [40]. Nucleotide‐binding proteins such as PI4K2A, RHOG, RAC1 and VCP (‘Valosin‐containing protein’) have been linked with genetic susceptibility of pituitary tumours [41].…”
Section: Resultsmentioning
confidence: 95%
“…PI4K2A also regulates VAMP3 involved in vesicular trafficking and GH secretion, which is already reported in rat pituicytes [38]. Protein PIP4K2A is involved in neuronal signal transduction and is a critical regulator for intracellular cholesterol transport [39], which has been reported as a biomarker gene candidate in bipolar disorder and depression [40]. Nucleotide‐binding proteins such as PI4K2A, RHOG, RAC1 and VCP (‘Valosin‐containing protein’) have been linked with genetic susceptibility of pituitary tumours [41].…”
Section: Resultsmentioning
confidence: 95%
“…SNPeff identified 8 as downstream variants, 46 as intergenic, 14 within introns, 5 upstream of genes and 2 in the 3’ UTR for WLI; 3 downstream variants, 51 within intergenic regions, 10 within introns, 4 upstream of genes, 1 in the 3’UTR, and 1 on a splice site/intron for WMI. Of these, two intron variants in WLI fell within HTR2C, a gene associated with depression 54 , 55 schizophrenia 56 , 57 , and stress response 58 , 59 . One intron variant on WLI fell within Il1rapl1, a gene associated with autism 60 , 61 and schizophrenia 62 .…”
Section: Resultsmentioning
confidence: 99%
“…Pathways include immune system [83], adaptive immune system [84], neutrophil degranulation [85], cytokine signaling in immune system [86] and GPCR ligand binding [87] were responsible for progression of COVID-19 infection. A previous study demonstrated that the expression levels of AHSP (alpha hemoglobin stabilizing protein) [88], IL7R [89], FBXO7 [90], KLRB1 [91], PIP4K2A [92], NFE2 [93], CCR2 [94], CLEC12A [95], NLRP12 [96], PECAM1 [97], TRIM10 [98], ICAM3 [99], EEF1A1 [100], CCR4 [101], PTPRC (protein tyrosine phosphatase receptor type C) [102], CX3CR1 [103], TSPAN32 [104], EOMES (eomesodermin) [105], ATM (ATM serine/threonine kinase) [106], CD28 [107], LRRK2 [108], CCL5 [109], CD33 [110], FCRL3 [111], CCR3 [112], FGL2 [113], GZMA (granzyme A) [114], PICALM (phosphatidylinositol binding clathrin assembly protein) [115], ALOX5 [116], MME (membrane metalloendopeptidase) [117], VIM (vimentin) [118], CD93 [119], GCA (grancalcin) [120], CD226 [121], CD1D [122], TNFSF4 [123], LEF1 [124], TLR4 [125], CCR7 [126], DPP4 [127], NLRC4 [128], ITGB3 [129], RASGRP1 [130], TLR2 [131], DOCK2 [132], CSF1R [133], PRKCB (protein kinase C beta) [134], CAMK4 [135], CXCL5 [136], CD36 [137], P2RY12 [138], LILRB2 [139], CD5 [140], SLC25A37 [141], ADIPOR1 [142], PECAM1 [143], RGS10 [144], RGS18 [145], ANK1 [146], RNF182 [147], NPRL3 [148], NINJ2 [149], KCNA3 [150], ABCG2 [151], MS4A6A [152], WDR45 [153], RAB39B...…”
Section: Discussionmentioning
confidence: 99%